HUBUNGAN POLA KONSUMSI, ASUPAN SERAT, KARBOHIDRAT SEDERHANA DAN KALIUM DENGAN KADAR TRIGLISERIDA PADA PASIEN PENYAKIT JANTUNG DI POLI PENYAKIT JANTUNG - Maigoda, Tonny C (JURNAL MEDIA KESEHATAN, 2012)
Deaths from heart and blood vessel disease in Indonesia by 26.3%. We assumed that only the low-fat diet will lower triglyceride levels, it is not entirely true. Since the main cause is excessive sugar consumption. It is therefore also important to avoid foods that are carbohydrates that have a high glycemic value, which is the glycemic value is how much carbohydrate that can be converted into sugar (Candra, 2010). The objectives of the study know the relationship between the pattern of consumption, fiber intake, simple carbohydrates and potassium in patients with triglyceride levels in the Heart Hospital M. Yunus. Obeservasional research method using cross-sectional design. Sampling in this study using non-probability sampling technique particularly with the way many as 123 people Proposive Sampling. By Karl Pearson correlation test, there is a strong relationship and patterned negative (p = 0.000) in this case based on the composition of the dish with triglyceride levels. There is a relationship between the intake of simple carbohydrates with triglyceride levels of heart disease patients (p = 0.004). It can be concluded that the dominant factor associated with triglyceride levels of heart disease patients are carbohydrates derived from food and beverage patients.